Strategi Kepemimpinan Kepala Madrasah Dalam Meningkatkan Mutu Pendidikan - yahya, fizian; Herawati, Nita Sunarya (Jurnal Manajemen dan Budaya, 2025)
Madrasah is a complex educational institution that has various dimensions, especially in madrasahs whose fiber maintains Islamic values, in addition to developing general sciences so that in leading a madrasah a mature strategy is needed. This study aims to analyze the leadership strategies employed by the principal of MA Al-Mannan Bagik Nyaka in enhancing the quality of input, process, and output, as well as to identify the inhibiting factors that affect these efforts. The research adopts a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the principal’s leadership strategies in improving the quality of education at MA Al-Mannan Bagik Nyaka include socialization through religious study group leaders and the implementation of several extracurricular activities. Among these, the *kitab kuning* program stands out as it is prioritized annually. Furthermore, the madrasah has achieved notable accomplishments, such as winning first place in the Qur’an memorization competition at the provincial level (NTB) and first place in a district-level rock-climbing competition. The institution has also experienced a steady increase in student enrollment. However, one of the major challenges in enhancing the quality of the madrasah is the intense competition among neighboring madrasahs.